Penerapan Sistem Database Dengan Menggunakan Aplikasi Dikbud HR Dalam Layanan Informasi Kepegawaian Dilingkungan ISBI Tanah Papua (Jurnal Manajemen Kreatif dan Inovasi, 2023)
Application of the database system using the Dikbud HR application in personnel information services within the Indonesian Cultural Arts Institute (ISBI) Tanah Papua. Dikbud HR is a special application designed to meet the needs of personnel administration in the fields of education and culture. The results of implementing the Dikbud HR application are to increase the efficiency and effectiveness of personnel administration at ISBI Tanah Papua. In this study, data was collected through interviews with related parties and retention analysis related to the implementation of Education and Culture HR at ISBI Tanah Papua. The results of the study show that the application of the Education and Culture HR application brings significant benefits. First, the database system allows storing employee data in a structured manner, facilitating the management of personal information, work history, training and employee achievements. Second, attendance and leave management becomes more efficient with electronic attendance records and an automated process for applying for leave. Third, employee payroll can be done automatically based on the risk of salary data, benefits and deductions stored in the database, reducing calculation errors and speeding up the payroll process. Fourth, the management of employee training and development becomes more effective with well-documented training history data. Fifth, reports and analysis generated from the system database enable management to obtain accurate information and deeper insights into employee performance and the effectiveness of staffing programs.